A new direction for health?. Issue 7577 (16th November 2006) - Tanne, Janice Hopkins
Abstract : Last week's victory for the Democratic party in the US mid-term elections is likely to mean changes in health care for senior citizens and uninsured people and less restriction on abortion, says Janice Hopkins Tanne